The Trojan Horse The Growth of Commercial Sponsorship - Philips, Deborah (Bloomsbury Academic, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The Trojan Horse traces the growth of commercial sponsorship in the public sphere since the 1960s, its growing importance for the arts since 1980 and its spread into areas such as education and health. The authors' central argument is that the image of sponsorship as corporate benevolence has served to routinize and legitimate the presence of commerce within the public sector. The central metaphor is of such sponsorship as a Trojan Horse helping to facilitate the hollowing out of the public sector by private agencies and private finance. The authors place the study in the context of the more general colonization of the state by private capital and the challenge posed to the dominance of neo-liberal economics by the recent global financial crisis. After considering the passage from patronage to sponsorship and outlining the context of the post-war public sector since 1945, it analyses sponsorship in relation to Thatcherism, enterprise culture and the restructuring of public provision during the 1980s. It goes on to examine the New Labour years, and the ways in which sponsorship has paved the way for the increased use of private-public partnerships and private finance initiatives within the public sector in the UK.